DEMOGRAPHIC DETERMINANTS OF ECONOMIC GROWTH IN INDIA: A POLICY-ORIENTED ANALYSIS - Raxmatov Firdavs Feruz o’g’li (Modern American Journals, 2025)
This study examines the impact of key demographic factors—healthcare, education, urbanization, investment, and labor dynamics—on India’s economic growth from 1991 to 2023. Using World Bank annual data and robust econometric techniques, including IRLS to address outliers, we estimate a model grounded in the Cobb-Douglas framework. Results highlight that increased investment, improved education spending (with a lag), and longer lifespan positively influence GDP growth, while rapid urban growth exerts negative pressure. Inflation and employment ratio changes also show significant effects. Findings align with the demographic dividend theory, emphasizing that strategic investments in healthcare and education can enhance productivity and economic well-being. However, regional disparities and cultural barriers limit equitable benefits. The study offers policy-relevant insights for optimizing resource allocation, underscoring the need for balanced, region-specific strategies to sustain growth while addressing the challenges of population aging and urbanization.
Keywords: India; economic growth; demographic factors; lifespan; sustainable development.